K2S2O8-mediated decarboxylative oxysulfonylation of cinnamic acids: A transition-metal-free synthesis of β-keto sulfones. Issue 34 (22nd August 2019) - Chawla, Ruchi; Kapoor, Ritu; Yadav, Lal Dhar S.
Graphical abstract: Highlights: Metal-free one-pot approach to β-keto sulfones. Use of air and K2 S2 O8 as eco-friendly and inexpensive oxidants. Decarboxylative oxysulfonylation of cinnamic acids. A synthetically useful radical pathway is developed. Abstract: A new paradigm of the oxidative decarboxylative sulfono functionalization of cinnamic acids with sulfinate salts mediated by K2 S2 O8 under aerobic conditions to afford synthetically and biologically relevant β-keto sulfones has been described. It is the first report on the transition-metal-free synthesis of β-keto sulfones from cinnamic acids, which employs environmentally benign, readily available and inexpensive starting materials and oxidants, viz. air and K2 S2 O8 .